2023
DOI: 10.1371/journal.pntd.0011285
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Typhi whole genome sequencing in Rwanda shows a diverse historical population with recent introduction of haplotype H58

Abstract: Salmonella enterica serovar Typhi (S. Typhi) is the cause of typhoid fever, presenting high rates of morbidity and mortality in low- and middle-income countries. The H58 haplotype shows high levels of antimicrobial resistance (AMR) and is the dominant S. Typhi haplotype in endemic areas of Asia and East sub-Saharan Africa. The situation in Rwanda is currently unknown and therefore to reveal the genetic diversity and AMR of S. Typhi in Rwanda, 25 historical (1984-1985) and 26 recent (2010-2018) isolates from Rw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Here, we found that at the region level, 4.3.1.1.EA1 dominated (78%, [95% CI 75.1–80.8%] n=647/830; see Figure 1a ). However, there were country-level differences, with 4.3.1.1.EA1 dominating in Malawi (94%; n=524/558), Tanzania (83%; n=15/18), Zimbabwe (80%; n=20/25), and earlier years in Kenya (59%, n=86/145 in 2012–2016), and 4.3.1.2.EA3 dominating in Rwanda (85%, n=23/27) ( Rutanga et al, 2023 ) and Uganda (97%, n=35/36) ( Figure 1b and Figure 1—figure supplement 3 ). Although the specific periods of sampling differ for these countries, the prevalence of H58 was consistently high across the available time frames for all countries, with no change in dominant genotypes (see Figure 1b and Figure 1—figure supplement 3 ; note the apparent shift to 4.3.1.2.EA3 in Kenya is based on n=4 isolates only so requires confirmation).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we found that at the region level, 4.3.1.1.EA1 dominated (78%, [95% CI 75.1–80.8%] n=647/830; see Figure 1a ). However, there were country-level differences, with 4.3.1.1.EA1 dominating in Malawi (94%; n=524/558), Tanzania (83%; n=15/18), Zimbabwe (80%; n=20/25), and earlier years in Kenya (59%, n=86/145 in 2012–2016), and 4.3.1.2.EA3 dominating in Rwanda (85%, n=23/27) ( Rutanga et al, 2023 ) and Uganda (97%, n=35/36) ( Figure 1b and Figure 1—figure supplement 3 ). Although the specific periods of sampling differ for these countries, the prevalence of H58 was consistently high across the available time frames for all countries, with no change in dominant genotypes (see Figure 1b and Figure 1—figure supplement 3 ; note the apparent shift to 4.3.1.2.EA3 in Kenya is based on n=4 isolates only so requires confirmation).…”
Section: Resultsmentioning
confidence: 99%